2013
DOI: 10.17795/jhealthscope-10496
|View full text |Cite
|
Sign up to set email alerts
|

Economic Consequence Analysis of Fire and Explosion in Petrochemical Feed and Product Pipelines Network

Abstract: Background: Economic consequence analysis is vital for recognizing pipeline comprehensive risk analysis and emergency response planning. Objectives: The purpose of this study was to estimate economic loss due to fire and explosion in petrochemical feed and product pipelines. Materials and Methods:The present study which performed on 47 pipelines of a petrochemical special zone, pertinent pipeline selected by chemical energy potential, flow rate and capital density. Pipeline hazard factor and material factor we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Accident analyses in big and process industries have indicated the important role of risk management system and its factors in accident investigation (1,2,8). Accordingly, analyzing and modeling of accidents' size in process industries was done on the basis of risk management system's factors, including S and H training, risk assessment, and risk control factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accident analyses in big and process industries have indicated the important role of risk management system and its factors in accident investigation (1,2,8). Accordingly, analyzing and modeling of accidents' size in process industries was done on the basis of risk management system's factors, including S and H training, risk assessment, and risk control factors.…”
Section: Discussionmentioning
confidence: 99%
“…This fact is mainly because of detrimental factors in these industries and complexity of the processes. Moreover, several studies have shown that there is a high rate of severe accidents, such as explosion, fire, release of toxic materials, and other minor and severe injuries in these industries (1,2).…”
Section: Introductionmentioning
confidence: 99%